The Effect of Competency Certification on Performance Mediated by Innovation - Pungky Nanda Raras; Eka Travilta Oktaria; Iskandar A.A; Andala Rama Putra Barusman; Habiburahman Habiburahman (Penerbit Goodwood, 2026)
Purpose: This study aimed to analyze the effect of competency certification on employee performance and examine the mediating role of innovation in strengthening this relationship. In the era of globalization and rapid technological advancement, organizations must continuously improve the quality of their human resources to remain competitive. Competency certification provides formal recognition of employees’ knowledge, skills, and professionalism. However, its impact on performance may be limited if not accompanied by innovative practices. Therefore, this study investigates whether innovation can function as a mechanism that enhances the effect of competency certification on employee performance. Methodology: This study used a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 20 respondents with experience in competency certification. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software to examine both direct and indirect relationships among variables. Results: The results indicate that competency certification positively and significantly affects employee performance, with a path coefficient of 0.662. Competency certification also positively affects innovation, with a coefficient of 0.416, and innovation influences performance, with a coefficient of 0.381. The mediation analysis shows that competency certification indirectly improves performance through innovation, with a value of 0.159, although the direct effect remains stronger. Conclusions: Innovation partially mediates the relationship between competency certification and employee performance. Limitations: This study was limited by its small sample size. Nevertheless. Contributions: This study contributes to the human resource management literature by highlighting the importance of integrating competency certification with innovation-oriented organizational practices.